Rekonstruksi Syarat Anggota Dewan Perwakilan Rakyat Dalam Perspektif Ketatanegaraan Islam - Muhammad Wahdini (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2020)
The many polemics that occur in the House of Representatives of the Republic of Indonesia (DPR RI), starting from the lack of the maximum legislative function where the Parliament is considered not productive in producing laws, instead of being productive, when producing Draft Laws actually results in highly controversial results. Like the latest Penal Code Bill, the Corruption Eradication Commission Law revised and caused turmoil in the community. Slanted news about legislative institutions in Indonesia has become a public secret, ranging from the lack of members present at meetings to those who are sleeping together and other issues. This research summarizes the opinions of thinkers in the world of Islamic state administration so that analyzing the capability or competence of DPR members is the main cause that causes a number of problems that occur. Furthermore, the concept of Islamic constitutionality answers that the professionalism and expertise aspects are the main priorities of those who fill positions in the legislature. So that there is a need to reconstruct the conditions of people who will fill the positions of DPR members needed by people who have capabilities and expertise in both the legislative, budgetary and supervisory functions. The estuary is the maximum performance of legislative members who are the presentations of all Indonesian people.